Lysine 63 ubiquitination is involved in the progression of tubular damage in diabetic nephropathy. Issue 1 (24th October 2016) - Pontrelli, Paola; Conserva, Francesca; Papale, Massimo; Oranger, Annarita; Barozzino, Mariagrazia; Vocino, Grazia; Rocchetti, Maria Teres.; Gigante, Margherita; Castellano, Giuseppe; Rossini, Michele; Simone, Simona; Laviola, Luigi; et al.
Abstract : The purpose of our study was to evaluate how hyperglycemia (HG)influences Lys63 protein ubiquitination and its involvement in tubular damage and fibrosis in diabetic nephropathy (DN). Gene and protein expression of UBE2v1, a ubiquitin‐conjugating E2‐enzyme variant that mediates Lys63‐linked ubiquitination, and Lys63‐ ubiquitinated proteins increased in HK2 tubular cells under HG. Matrix‐assisted laser desorption/ionization–time of flight/tandemmass spectrometry identified 30 Lys63‐ubiquitinated proteins, mainly involved in cellular organization, such as β‐actin, whose Lys63 ubiquitination increased under HG, leading to cytoskeleton disorganization. This effect was reversed by the inhibitor of the Ubc13/UBE2v1 complexNSC697923. Western blot analysis confirmed that UBE2v1 silencing in HK2 under HG, restored Lys63‐β‐actin ubiquitination levels to the basal condition. Immuno histochemistry on patients with type 2 diabetic (T2D) revealed an increase in UBE2v1‐ and Lys63‐ubiquitinated proteins, particularly in kidneys of patients with DN compared with control kidneys and other nondiabetic renal diseases, such as membranous nephropathy. Increased Lys63 ubiquitination both in vivo in patients with DN and in vitro, correlated with α‐SMA expression, whereas UBE2v1 silencing reduced HG‐induced α‐SMA protein levels, returning them to basal expression. In conclusion, UBE2v1‐ and Lys63‐ubiquitinated proteins increase in vitro under HG, as well as in vivo in T2D, is augmented in patients with DN, and may affect cytoskeleton organization and influence epithelial‐to‐mesenchymal transition. This process may drive the progression of tubular damage and interstitial fibrosis in patients with DN.—Pontrelli, P., Conserva, F., Papale, M., Oranger, A., Barozzino, M., Vocino, G., Rochetti, M. T., Gigante, M., Castellano, G., Rossini, M., Simone, S., Laviola, L., Giorgino, F., Grandaliano, G., DiPaolo, S., Gesualdo, L. Lysine 63 ubiquitination is involved in the progression of tubular damage in diabetic nephropathy. FASEB J. 31, 308–319 (2017) www.fasebj.org